The great flood-gates of the wonder-world flung open - Rasmus Grøn (Akademisk Kvarter, 2012)
The first part of the article describes how the novel Moby Dick stages the journey as a Romantic American cultural project and at the same time establishes a modern room of experience in which this project is emptied of metaphysical content. In the second and third parts this is the foundation of an analysis of the main characters of the novel. Ahab and Ishmael, who represent two complementary perspectives of experience of the journey as existential, subjective project. In the final part of the article it is demonstrated how the relation between these two positions of subjects form the background of both the compositional tension between plot and digression as well as the novel's genre and its enunciation.